Impact of Leadership and Professionalism on Teacher Performance with Quality Management as Mediator - Jayadi, Usman; Farida Ferine, Kiki (PT. Multidisciplinary Press Indonesia, 2024)
This study investigates the effects of principal leadership and teacher professionalism on teacher performance in Mataram City, with a focus on the role of education quality management as a mediator. Using a quantitative approach and Partial Least Square (PLS) analysis, the findings show that while principal leadership does not significantly affect quality management, it directly influences teacher performance. Conversely, teacher professionalism impacts both quality management and teacher performance. Quality management does not directly affect teacher performance, but teacher professionalism enhances it through quality management, highlighting its crucial role in improving educational outcomes.